Antitumor activity of α‐pinene in T‐cell tumors - Abe, Masaya; Asada, Noboru; Kimura, Maiko; Fukui, Chie; Yamada, Daisuke; Wang, Ziyi; Miyake, Masayuki; Takarada, Takeshi; Ono, Mitsuaki; Aoe, Michinori; Kitamura, Wataru; Matsuda, Masayuki; et al. (Cancer science, 2024)
T‐cell acute leukemia and lymphoma have a poor prognosis. Although new therapeutic agents have been developed, their therapeutic effects are suboptimal. α‐Pinene, a monoterpene compound, has an antitumor effect on solid tumors; however, few comprehensive investigations have been conducted on its impact on hematologic malignancies. This report provides a comprehensive analysis of the potential benefits of using α‐pinene as an antitumor agent for the treatment of T‐cell tumors. We found that α‐pinene inhibited the proliferation of hematologic malignancies, especially in T‐cell tumor cell lines EL‐4 and Molt‐4, induced mitochondrial dysfunction and reactive oxygen species accumulation, and inhibited NF‐κB p65 translocation into the nucleus, leading to robust apoptosis in EL‐4 cells. Collectively, these findings suggest that α‐pinene has potential as a therapeutic agent for T‐cell malignancies, and further investigation is warranted. α‐Pinene inhibited the proliferation of T‐cell tumor cell lines, induced mitochondrial dysfunction and reactive oxygen species accumulation, and inhibited NF‐κB p65 translocation into the nucleus, leading to robust apoptosis in tumor cells.